A Mouse Model of Small-Vessel Disease that Produces Brain-Wide-Identified Microocclusions and Regionally Selective Neuronal Injury. Issue 5 (May 2015) - Silasi, Gergely; She, Jennifer; Boyd, Jamie D; Xue, Songchao; Murphy, Timothy H
We developed a mouse model of small-vessel disease where occlusions are produced through endovascular injection of fluorescent microspheres that target 12 μm diameter penetrating arterioles and can be localized in histology. Using Thy1-GFP transgenic mice, we visualized the impact of microocclusions on neuronal structure. Microocclusions in the hippocampus produce cell loss or neuronal atrophy ( 7% of lodged microspheres led to microinfarcts), while axons within white matter tracts, as well as the striatum and thalamus became blebbed or disrupted. Although the neocortex contained more occlusions than other structures, labeled layer 5 neurons were relatively resistant to structural damage, with <2% of the lodged microspheres producing obvious neuronal damage.